Do Couples Bargain over Fertility? New Evidence Based on Child Preference Data - Timo Hener (Verein für Socialpolitik, 2010)
Theoretical and empirical research has shown that households should not be considered as single decision units, but as consisting of heterogeneous individuals who bargain over household resource allocations. In this paper we present evidence that couples also bargain over fertility. In contrast to earlier tests of bargaining models, our empirical approach makes use of child preference data from the German Socio-Economic Panel (GSOEP) to make inferences about whether bargaining power matters for fertility decisions. Our results also indicate that couples are not able to fully commit to household resource allocations. As women usually have lower incomes and higher child preferences than men, a policy implication of our findings is that the effect of child benefits on fertility could be enhanced by directing transfers to women.
Keywords: J13; J18; D01; 330; Fertility; Child Benefits; Preferences; Intra-Household Allocation; Bargaining; Limited Commitment